Expiratory Flow Limitation at Different Exercise Intensities in Coronary Artery Disease - Viviane Castello-Simões; Marlus Karsten; Vinicius Minatel; Rodrigo Polaquini Simões; Ester Silva; Nayara Yamada Tamburús; Ross Arena; Audrey Borghi-Silva; Aparecida Maria Catai (Cardiology Research and Practice)
Introduction. Expiratory flow limitation (EFL) during moderate intensity exercise is present in patients with myocardial infarction (MI), whereas in healthy subjects it occurs only at a high intensity. However, it is unclear whether this limitation already manifests in those with stable coronary artery disease (CAD) (without MI). Materials and Methods. Forty-one men aged 40–65 years were allocated into (1) recent MI (RMI) group (n = 8), (2) late MI (LMI) group (n = 12), (3) stable CAD group (n = 9), and (4) healthy control group (CG) (n = 12). All participants underwent two cardiopulmonary exercise tests at a constant workload (moderate and high intensity), and EFL was evaluated at the end of each exercise workload. Results. During moderate intensity exercise, the RMI and LMI groups presented with a significantly higher number of participants with EFL compared to the CG (p<0.05), while no significant difference was observed among groups at high intensity exercise (p>0.05). Moreover, EFL was only present in MI groups during moderate intensity exercise, whereas at high intensity all groups presented EFL. Regarding the degree of EFL, the RMI and LMI groups showed significantly higher values at moderate intensity exercise in relation to the CG. At high intensity exercise, significantly higher values for the degree of EFL were observed only in the LMI group. Conclusion. The ventilatory limitation at moderate intensity exercise may be linked to the pulmonary consequences of the MI, even subjects with preserved cardiac and pulmonary function at rest, and not to CAD per se.